Yet another case of Nordic exceptionalism? A quantitative approach to an intra-Nordic and an international comparison of supreme courts' constitutional reasoning - Nicklas Pettersson; Katalin Kelemen (Örebro University School of Business, 2024)
We present a systematic quantitative approach how to analyze the reasons that judges in Nordic countries publicly adduce for their decisions in constitutional matters, as implemented in the Nordic CONREASON Project. Based on encodings of forty (per court) purposively selected landmark cases, common traits and patterns of constitutional argumentative practices in each of the Nordic supreme courts were identifted and an international comparison were made to courts from related studies. Our results provided strong support that, regarding speciftc aspects (on a univariate level), one or more courts typically tended to deviate from the other Nordic courts. Also, in a multivariate worldwide comparison there were variation between the Nordic supreme courts. However, although not detached from other supreme courts, the Nordic supreme courts seemed to occupy an area of their own on the international map of constitutional reasoning.
Keywords: C10; C38; C53; K10; K40; N40; 330; constitutional reasoning; quantitative comparative law; empirical legal studies; Nordic exceptionalism; realist decision-making